Sistem Pendukung Keputusan dalam Menentukan Kualitas Lateks pada Tanaman Karet Menggunakan Matlab dengan Metode Fuzzy Mamdani (Studi Kasus PT. Gergas Utama Kecamatan Wampu Kabupaten Langkat) - Sinuhaji, Nirwan; Ginting, Raheliya Br.; Puspita, Erni (MEANS (Media Informasi Analisa dan Sistem), 2020)
Rubber plant is one of plants that produces latex which can be used as materials production of vehicle tools, health equipment, mat and other kinds of equipment. In PT Gergas Utama, Wampu Sub-district, District of Langkat, a good and proper quality of ruber plants are still determined by applying conventional method of Meter Lock usage. The criteria to produce International standard Latex are the age of rubber plants, winding width, and climate or weather. In the research, the Mamdani Fuzzy method was applied as the Decision Support System in order to determine the best quality of latex which can optimize the time and can overcome failures in determining latex quality. Fuzzy variables used in the research are the age of rubber plants, winding width, and climate or weather. The Fuzzy set used in each variable are is young (0-6), medium (3-12), old (9-15), small ( 0-0.8 ), medium (0.4-1.6 ), big (1.2 -2 ), rain ( 0-20 ), transition ( 15-30 ), dry (25-35). Fuzzy Mamdani method consists of Fuzzification, Rule Formation, Inference Engine, Defuzzification and Matlab Programming